Fafiliss Enterprise / Nurul Afiqah Mohd Rashid...[et al.] - Mohd Rashid, Nurul Afiqah; Mohd Nor, Seri Suraya; Kamaruzzaman, Fatin Nadiah; Mohd Sapee, Nazliya (2012)
Fafiliss Enterprise is a partnership form of business consisting 4 partners with four positions and act as General Manager , Operational Manager , Marketing Manager and Financial Manager.To make sure our business run smoothly , we agree cooperate to working at front of the house using our work schedule besides working at the back of the house we hire additional worker. Butter stick is creation of new innovation to the packaging of butter. Other than that , the butter stick is easy to use. So , Fafiliss Enterprise had launched a new product named Butter Stick that will give the solution for everyone who are still searching easier way to have a meal and make a meal. It can be taken at any time and easy for travel since it is in small case. It also can be consumed by spreading on bread or others surfaces.